PENGARUH INFLASI, INTELLECTUAL CAPITAL, DAN RETURN ON ASSETS TERHADAP RETURN SAHAM PADA MASA PANDEMI COVID-19 (SURVEI PADA PERUSAHAAN FOOD AND BEVERAGE YANG LISTING DI BURSA EFEK INDONESIA DARI TAHUN 2019 SAMPAI 2021) - Marion Attila, Almudatsir; Wijaya, Rico; Wiralestari (Jurusan Akuntansi FEB Universitas Jambi, 2024)
This research aims to examine the influence of inflation, intellectual capital, and return on assets on stock returns during the Covid-19 pandemic. The population of this research is food and beverage companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. The data collection method used in this research is purposive sampling. Based on the purposive sampling method, the total sample obtained in this research was 27 food and beverage companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. Hypothesis testing in this research was carried out using the multiple linear regression analysis method. The results of this research show that inflation and return on assets have a significant influence on stock returns in food and beverage companies. Meanwhile, intellectual capital does not have a significant effect on stock returns in food and beverage companies